Association Between Conservative Treatment Modalities and Clinical Outcomes in Patients With Lumbosacral Disc Herniation Following Short Term and Long Term Treatments: A Retrospective Cohort Study - Bina Eftekharsadat; Shadi Khodaei; Raha Markazi‐Movaghar; Fatemeh ojaghlou; Azizeh Farshbaf‐Khalili; Soraya Babaie (Health Science Reports, 2026)
ABSTRACT Background and Aims Lumbar disc herniation (LDH), a leading cause of low back pain, necessitates effective conservative management to mitigate surgical interventions. This retrospective observational study evaluated the short‐term (6 months–2 years) and long‐term (3–6 years) efficacy of conservative therapies in 194 LDH patients from Iran. Methods Data were collected via medical records, demographic questionnaires, and the numerical rating scale (NRS) for pain, with analyses adjusting for covariates such as body mass index (BMI), comorbidities, and treatment modalities. Data were analyzed using SPSS 24 (Kolmogorov–Smirnov normality test), including descriptive (frequencies, means/SDs) and inferential statistics ( t ‐tests, ANOVA, chi‐square, Fisher's exact); ANCOVA and multivariate logistic regression (adjusted for confounders, 95% confidence interval CI) modeled pain/paresthesia outcomes. Results The s ignificant pain reduction after treatment (mean NRS: 7.3 to 3.7, p < 0.001) was demonstrated with home exercise programs showing the largest improvement (adjusted β : −0.74, p = 0.010). Short‐term pharmacological therapy (≤ 24 months) also reduced pain ( β = −0.96, p = 0.02), while long‐term use lacked efficacy. Higher BMI correlated with higher pain ( p = 0.03) and paresthesia risk ( p = 0.01), and water therapy unexpectedly increased paresthesia odds (odds ratio (OR) = 4.14, p = 0.03) compared to other treatments. Females reported higher paresthesia rates (52.7% vs. 33.3%, p = 0.03), and comorbidities like hypertension were associated with a higher rate of paresthesia. Satisfaction rates exceeded 66% across therapies, though adherence to acupuncture, yoga, and injections was low. Conclusion The findings suggest that home‐based exercise and short‐term pharmacological therapy were associated with more favorable pain outcomes in this cohort. However, due to the observational design, these findings should be interpreted as associations rather than evidence of causal treatment effectiveness.